Funding sources in mobile payments systems - Michał Kisiel (Copernican Journal of Finance & Accounting, 2013)
The article aims to propose the classification of mobile payments systems based on the prevailing type of funding sources and the settlement mechanisms. The main types of mobile payments systems were presented, followed by the proposed list of conceptual models. The research based on analysis of business models used by m- -payments systems worldwide shows that the choice of funding sources is wide. Few of them are almost completely independent of interbank payment systems, effectively creating the alternative flow of monetary value.